2015
DOI: 10.5694/mja15.01068
|View full text |Cite
|
Sign up to set email alerts
|

Hospital doctors' Opinions regarding educational Utility, public Sentiment and career Effects of Medical television Dramas: the HOUSE MD study

Abstract: This survey shows that a large body of the medical workforce watches medical television dramas and that such programs exercise a growing influence on the practice of junior doctors, particularly those in physicianly specialties. The reasons for certain role model selections remain unknown and may require further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Katherine Lingenfelter, supervising producer of “House MD”, views it as a social responsibility in fictional series, such as “House MD”, to keep the scientific facts as correct as possible [ 12 ]. Of course these dramas main purpose has been one of entertainment and they are never completely representative of daily practice [ 13 ]. However, these characteristics could make the knowledge mediation more attractive.…”
Section: Discussionmentioning
confidence: 99%
“…Katherine Lingenfelter, supervising producer of “House MD”, views it as a social responsibility in fictional series, such as “House MD”, to keep the scientific facts as correct as possible [ 12 ]. Of course these dramas main purpose has been one of entertainment and they are never completely representative of daily practice [ 13 ]. However, these characteristics could make the knowledge mediation more attractive.…”
Section: Discussionmentioning
confidence: 99%
“…If he or she becomes a member of the medical profession in the future, they will be confronted with dilemmas involving standard principles of medical ethics. According to one study, junior doctors who watch medical dramas are more likely to be inspired and influenced by the content of such dramas [18]. Without valid reason, the non-medical audience may suspect that all health staff members are obsessive in sexual relationships with patients or among themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies in this area have measured medical students’ or current medical staffs’ opinions and perceptions of medical TV shows. For example, Haboubi et al 19 surveyed medical doctors of all grades to measure their reasons for and frequencies of watching medical TV shows. They discovered that a large portion of physicians watch such programs and that some even use them as a source of medical information.…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that a large portion of physicians watch such programs and that some even use them as a source of medical information. 19 In their observational study, Lapostolle et al 20 reported that the population (patients) and examinations (tests and procedures) in the TV show House M.D. were unrealistic.…”
Section: Discussionmentioning
confidence: 99%